2008
DOI: 10.1097/aog.0b013e3181801d56
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Prevention of Recurrent Preeclampsia

Abstract: Women with a history of previous preeclampsia are at increased risk of preeclampsia and other adverse pregnancy outcomes in subsequent pregnancies. The magnitude of this risk is dependent on gestational age at time of disease onset, severity of disease, and presence or absence of preexisting medical disorders. The objective in the management of these patients is to reduce risk factors by optimizing maternal health before conception and to detect obstetric complications as early as possible. This objective can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
182
0
21

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(213 citation statements)
references
References 97 publications
10
182
0
21
Order By: Relevance
“…Maternal age below 30 years appeared to be protective in this study. This finding correlates with other similar studies 2,7 . Maternal level of education was found to have no significant relationship to the development of pre-eclampsia just like previous studies where the level of education was not found to be a significant risk factor 12,25 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Maternal age below 30 years appeared to be protective in this study. This finding correlates with other similar studies 2,7 . Maternal level of education was found to have no significant relationship to the development of pre-eclampsia just like previous studies where the level of education was not found to be a significant risk factor 12,25 .…”
Section: Discussionsupporting
confidence: 83%
“…It is a disorder characterized by vasoconstriction, metabolic changes, endothelial dysfunction, and activation of the coagulation cascade in conjunction with an inflammatory response 4 . Pre-eclampsia complicates 3-5% of first pregnancies and 1% of subsequent pregnancies with around 5-10% of cases being severe 2 . In Nigeria, a prevalence rate of 5.6% has been reported 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, these findings support an expected beneficial effect of antioxidant therapy in the prevention of PE and other pregnancy-related disorders 61 . Numerous studies have been carried out to investigate prophylactic and/or therapeutic prevention of oxidative stress and the impact on PE and its perinatal complications 62. Despite the logic behind using antioxidant vitamins, several studies show that Vitamin C/E supplementation is of no benefit and may in fact cause harm 63 .…”
Section: Antioxidantssupporting
confidence: 57%
“…Other factors include a partner who fathered preeclamptic pregnancy with another woman, woman born as small for gestational age, and adverse outcomes in a previous pregnancy 7 . Women with a history of preeclampsia also develop cardiovascular disease later in their life.…”
Section: Introductionmentioning
confidence: 99%